2018
DOI: 10.1088/1674-1137/42/9/093103
|View full text |Cite
|
Sign up to set email alerts
|

Glueball spectrum from N f = 2 lattice QCD study on anisotropic lattices

Abstract: The lowest-lying glueballs are investigated in lattice QCD using N f = 2 clover Wilson fermion on anisotropic lattices. We simulate at two different and relatively heavy quark masses, corresponding to physical pion mass of mπ ∼ 938 MeV and 650 MeV. The quark mass dependence of the glueball masses have not been investigated in the present study. Only the gluonic operators built from Wilson loops are utilized in calculating the corresponding correlation functions. In the tensor channel, we obtain the ground stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
(126 reference statements)
1
48
0
Order By: Relevance
“…The authors get the result m η = 1019(119) MeV at the physical pion mass consistent with the physical η mass. Similar lattice studies have also been carried out in the N f = 2 case [8,28]. In Ref.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The authors get the result m η = 1019(119) MeV at the physical pion mass consistent with the physical η mass. Similar lattice studies have also been carried out in the N f = 2 case [8,28]. In Ref.…”
Section: Discussionmentioning
confidence: 67%
“…In Ref. [8], the authors get the mass of the isoscalar pseudoscalar η 2 to be m η2 = 890(38) MeV at m π = 650 MeV. In Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these resonances is not understood at present and a tensor glueball has still not been clearly identified. According to lattice-QCD simulations, the lightest tensor glueball has a mass between 2.2 and 2.4 GeV; see, e.g., [44][45][46][47][48][49][50]. The f 2 (2300) and f 2 (2340) states are good candidates to be tensor glueballs.…”
Section: Introductionmentioning
confidence: 99%
“…Most lattice results have been obtained in the quenched approximation 1 , i.e. without dynamical quarks, but recent unquenched lattice calculations [18][19][20] have found no evidence for significant unquenching effects, which however should be expected if the pseudoscalar glueball were to mix strongly with radially excited η( ) mesons. Moreover, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ref. [20] recently reported that correlation functions of pseudoscalar gluonic operators built from Wilson loops did not show any trace of the flavor singlet pseudoscalar meson states which can be found in the topological charge density correlator. In fact, on the experimental side it is still a controversial issue whether as many as three states η(1295), η(1405), and η(1475) (and thus indication of the involvement of the pseudoscalar glueball in this mass region) really exist.…”
Section: Introductionmentioning
confidence: 99%